Perceptions of Beauty and Identity: The Skin Bleaching Phenomenon in Jamaica - Petra A. Robinson (Adult Education Research Conference, 2011)
Founded on the significance of the skin bleaching phenomenon in Jamaica, and the persistent influences of colonialism, the purpose of this paper is twofold: (a) to explore the skin bleaching phenomenon and (b) to provide a snapshot of how colonialism (despite national independence) influences perceptions of beauty and identity in Jamaica, particularly through informal learning. Based on an empirical study, the research sought to explore and understand the perceptions and motivations behind the practice of skin bleaching, given the historical and social context, and how it influenced the participants’ perceptions of beauty and identity
Keywords: colorism; postcolonialism; skin color; informal learning; identity